Luteinizing hormone release and plasma metabolites in mature, ovariectomized beef cows fed various lipid diets - C.W. Peters; L.R. Corah; R.C. Cochran (Kansas Agricultural Experiment Station Research Reports, 1993)
Feeding rumen-escape lipid or soybean oil in a range supplement to beef cow resulted in elevated blood cholesterol and enhanced luteinizing hormone (LH) release compared to a control (milo and soybean meal) supplement. Cholesterol was elevated (P<.01) within 14 d of lipid feeding. The amplitude of each LH pulse and maximal pulse height were greater (P<.05) when cows were fed high-lipid diets. The positive influence of high-lipid diets on reproductive function may be explained in part by enhanced LH release.
Keywords: Cattlemen' s Day; 1993; Kansas Agricultural Experiment Station contribution; no. 93-318-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 678; Beef; Beef cows; Lipid; Luteinizing hormone; Cholesterol; Reproduction